Probing the dipolar coupling in a heterospin endohedral fullerene-phthalocyanine dyad - Zhou, S; Yamamoto, M; Briggs, G; Imahori, H; Porfyrakis, K (American Chemical Society, 2016)
Paramagnetic endohedral fullerenes and phthalocyanine (Pc) complexes are promising building blocks for molecular quantum information processing, for which tunable dipolar coupling is required. We have linked these two spin qubit candidates together and characterized the resulting electron paramagnetic resonance properties, including the spin dipolar coupling between the fullerene spin and the copper spin. Having interpreted the distance-dependent coupling strength quantitatively and further discussed the antiferromagnetic aggregation effect of the CuPc moieties, we demonstrate two ways of tuning the dipolar coupling in such dyad systems: changing the spacer group and adjusting the solution concentration.